A 5-year prospective validation of the Miller-McEntire Periodontal Prognostic Index - Gopalakrishnan Dharmarajan; Preston Dallas Miller; Robert A Levine; Sangamithra Sidharthan; Amit Vasant Mahuli; Prathip Phantumvanit; Borvornwut Buranawat (Wolters Kluwer Medknow Publications, 2022)
Background: This 5-year prospective survival analysis study aimed to examine the prognostic validity of a periodontal prognostic score specific for diseased molars: Miller-McEntire Periodontal Prognostic Index (MMPPI). Materials and Methods: One thousand and twenty-three molars were evaluated from 129 patients. The MMPPI scoring factors included age, smoking, diabetes, probing depth, mobility, molar type, and furcation involvement. MMPPI was computed as the sum of scores for all seven prognostic factors. Appropriate periodontal treatment and supportive periodontal therapy were provided. All patients were evaluated at baseline and annually posttreatment up to 5 years. Hazard risk ratios (HR) were computed for each prognostic factor, MMPPI scores assigned. The MMPPI score were then analyzed using Kaplan-Meier survival analyses. Results: A total of 31/1023 (0.3%) molars were extracted over the 5-year follow-up duration. Significant and positive hazard risk ratio (HR = 1.9) was noted for the total MMPPI score, validating its prognostic value for molar survival at 5 years prospectively. Kaplan-Meier survival analysis showed a significantly lower probability of molar survival with increasing MMPPI scores, where total score >8 showed worse survival probability over time. The hazard risk ratio was significant for individual prognostic factors: mobility (HR = 1.63), smoking (HR = 1.61), diabetes mellitus (DM) (HR = 1.4), molar type (1.97), and furcation involvement (2.22). Conclusions: The findings of the current study demonstrate significant prognostic validity of MMPPI scores for molar loss for 5 years, and a score >8 showed markedly worse molar survival probability in a well-maintained, university-based, prospective cohort. Mobility, smoking, DM, molar type, and furcation were component factors that were significant individual predictors.